(untitled) (Cultura Económica, 2019)
This article is a reflection based on the report “Employment and Social Development” produced by the researchers Jorge Colina, Osvaldo Giordano and Marcelo Marzocchini of the Department of Economics of the Catholic University of Argentina. Using the Gini index for the different regions of the country, the author shows the enormous differences in the income distribution between the Central, South and North regions of Argentina. Such differences have evident consequences that are not currently considered by the national government’s public policies in relation to provincial governments and impoverished regions. The article proposes decentralization as a means for the development of each region.